Changes in Policy and Endoscopic Procedures during the 2019 Coronavirus Disease Outbreak: A Single Center Experience - Adi Lahat; Avidan Benjamin (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims The coronavirus disease-19 (COVID-19) pandemic forced endoscopy units to enact major changes on daily practice and policy. The Chaim Sheba Medical Center is a tertiary referral center located in the center of Israel, and serves cities with high infection rates. Our aim was to review the policies enacted during this outbreak and study their influence on the performance of endoscopic procedures. Methods Following the revision of work protocols, personnel were divided into two permanent and physically separate working groups and screening procedures were rescheduled. Relevant data including the number of endoscopic examinations, type of procedure performed, and patient referrals and indications were taken from a computerized database and evaluated. The study included data for January-March 2018-2020, and a comparison among the data from each year was performed. Results As of March 2020, the total number of endoscopic examinations performed reduced by 44% (p<0.0001) as compared to previous years, gastroscopy examinations reduced by 39% (p=0.02), and lower endoscopy procedures reduced by 57% (p<0.0001). Meanwhile, the number of advanced endoscopic procedures performed remained consistent with previous years. The indications for performance of gastroscopy and lower endoscopy were different in March 2020, while these remained unchanged for advanced endoscopic procedures. Conclusions The current policy appears to serve both our initial goals: protecting personnel and patients' safety and minimizing potential damage from delayed endoscopic procedures. A longer term follow-up study is needed in order to fully analyze our results.